2021
DOI: 10.1007/s11356-021-14492-3
|View full text |Cite
|
Sign up to set email alerts
|

E-waste polycyclic aromatic hydrocarbon (PAH) exposure leads to child gut-mucosal inflammation and adaptive immune response

Abstract: Polycyclic aromatic hydrocarbon (PAH) exposure alters immunological responses. Research concerning PAH exposure on intestinal immunity of children in electronic waste (e-waste) areas is scarce. The aim of this study was to evaluate the effects of polycyclic aromatic hydrocarbon (PAH) pollutants on intestinal mucosal immunity of children in e-waste areas. Results showed higher hydroxylated PAH (OH-PAH) concentrations in e-waste-exposed children, accompanied with higher sialyl Lewis A (SLA) level, absolute lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Moreover, the co-exposure of OH-PAHs and mPAEs has been a concern due to humans being commonly exposed to a mixture of OH-PAHs and mPAEs in real environmental scenarios. However, most current studies separately explored the adverse effects of OH-PAHs or mPAEs exposure on inflammatory indicators [17,42,43]. In contrast, we explored co-exposure to OH-PAHs and mPAEs, considering the realistic exposure scenarios and the results showed that co-exposure to OH-PAHs and mPAEs was also associated with elevated inflammatory indicators, and MOP acts as a major contributor.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the co-exposure of OH-PAHs and mPAEs has been a concern due to humans being commonly exposed to a mixture of OH-PAHs and mPAEs in real environmental scenarios. However, most current studies separately explored the adverse effects of OH-PAHs or mPAEs exposure on inflammatory indicators [17,42,43]. In contrast, we explored co-exposure to OH-PAHs and mPAEs, considering the realistic exposure scenarios and the results showed that co-exposure to OH-PAHs and mPAEs was also associated with elevated inflammatory indicators, and MOP acts as a major contributor.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies found that PAH exposure, including parental occupational exposure to car exhaust, smoking, and proximity to transportation routes, is related to the risk of childhood leukemia(Weng et al 2008 ). Although the research results are inconsistent, the relevant results suggested that PAH exposure increases the risk of ALL and affects the disease process(Chen et al 2021a ; Zhang et al 2021a ; Enuneku et al 2021 ). Moreover, its regulatory mechanism appears related to the aryl hydrocarbon receptor (AHR) (O'Driscoll et al 2018 ; Tao et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%